SELECTING THE PREFERRED ALGORITHM FOR THE EMBEDDING OF DIGITAL WATERMARKS INTO VIDEOFILES - Shostak, N. V.; Bezruk, V. M.; Astrakhantsev, A. A. (Radio Electronics, Computer Science, Control, 2018)
ABSTRACT Context. Recently, the number of attacks on intellectual property has increased significantly, which, according to the polls, occupies a leading position in the structure of modern society. The comprehensive development of the country is impossible without generating its own intellectual data and their protection, which, in the face of information wars, is the most urgent task in modern society. Since intellectual data must not only be generated and stored, but also transmitted through open communication channels, the importance and urgency of the study of the stability of methods for protecting intellectual data to the effect of interference in channels is increasing. This work is dedicated to solving this urgent task. Objective – definition of a steganographic algorithm for hiding a digital watermark in a video container optimal for performance criteria, resistance to attacks, concealment and bandwidth using software simulation and hierarchy analysis method. Method. The algorithms for embedding of digital watermarks in a moving image are considered. Recently, much attention has been paid to embedding algorithms that have properties such as resistance to attacks and the concealment of embedded information. These algorithms can be classified by the type of area in which the digital watermark is embedded or seized, their bandwidth, realtime performance, and resistance to specific attack types. Existing embedding algorithms in a video can be conventionally divided into three main groups, depending on the area in which the embedded digital watermark: embedding methods in the spatial domain, in the region of transformation, and embedding methods in video compressed by the MPEG standard. The embedding algorithms of the digital watermark in the spatial area are used for uncompressed video. The embedding digital watermark is usually added to the brightness component and some color components, or only to the color components. In embedding algorithms in the transformation region, the watermark is distributed over the transformation region and difficult to remove after embedding. For methods in the field of transformation, there are several classes of methods based on different transformation functions, the main of which are the discrete cosine transform, discrete wavelet transform and discrete Fourier transform. Results. As a result of calculations the choice of the preferred algorithm of concealment of digital watermarks in a video file was made. Conclusions. In this article, a hierarchy analysis method is used to determine the preferred algorithm for integrating information into video files according to a combination of quality indicators. The preferred algorithm is obtained on the basis of existing matrices of comparisons of the relative importance of quality indicators and the results of software modeling of steganographic embedding algorithms in video files. If the bandwidth was chosen as the prevailing criterion, the best method based on this criterion is provided by a method based on the LSB, which is enhanced by the additional use of the Hamming code with the value of the priority vector 0.24. When the resistance to attacks was used as the predominant criterion, the results of the studies showed the effectiveness of the discrete wavelet transform method with the possibility of embedding 2 bits of the digital watermark in the DCT block into the frequency domain of LH. The scientific novelty of the work is that for the first time the method of embedding in the video file was prevailing on the criteria of speed, bandwidth and resistance to interference in communication channels, and the theory of concealing information in video files was further developed by increasing the noise immunity of existing algorithms. The practical significance of the work is determined by the applicability of the investigated algorithms for protecting intellectual property on video products transmitted by channels of communication with the obstacles, the solution of this problem is an actual problem in the modern world.